The Effect of Fragment C of Tetanus Toxin on Memory Deficits in a Rat Model of Alzheimer’s Disease - OZSOY, Seyma; DELIBAS, Elif Azize Ozsahin (International Journal of Computational and Experimental Science and Engineering, 2023)
The progression of Alzheimer’s disease (AD) is connected to both neuronal elements and immunological mechanisms. Tetanus toxin C-terminal fragment (TTC) has neuroprotective properties. Our objective was to examine the influence of TTC on memory, hippocampal morphology, and inflammation in rats with a STZ-induced AD model. After general anesthesia rats, 3 mg/kg STZ was administered ICV to the right and left lateral ventricles of 5 μl of 12 rats. Six rats were received both lateral ventricules of 0.9% NaCl 5 µl ICV, and others were administered TTC (0.05 flocculation units) in 5 µl ICV one time. No drug was applied to the control group. On the 15th day, all groups underwent a passive avoidance learning (PAL) test, and then brain tissue was collected. Tumor necrosis factor-alpha (TNF-α) and interleukin 6 (IL-6) levels within the brain were assessed. Following this, neurons were quantified by employing Cresyl violet staining specifically within the hippocampal CA1 and CA3 regions. In the ICV-STZ group, the PAL latency time significantly reduced, TNF-α levels and IL-6 levels increased, and also the hippocampal CA1 and CA3 neuron numbers decreased. The application of TTC resulted in a significant decrease in the levels of TNF-α and IL-6. Furthermore, it played a role in mitigating the memory impairment caused by ICV-STZ by reducing cell death within the hippocampus. These results suggest that the neuroprotective and antiinflammatory properties of TTC might have a significant impact on addressing neurodegenerative disorders such as Alzheimer’s disease.